The Long-Term Causal Effects of Winning an ERC Grant - Corinna Ghirelli; Enkelejda Havari; Elena Claudia Meroni; Stefano Verzillo (Institute of Labor Economics (IZA), 2023)
This paper investigates the long-term causal effects of receiving an ERC grant on researcher productivity, excellence and the ability to obtain additional research funding up to nine years after grant assignment. We use data on the universe of ERC applicants between 2007-2013 and information on their complete publication histories from the Scopus database. For identification, we first exploit the assignment rule based on rankings, comparing the outcomes of the winning and non-winning applicants in a regression discontinuity design (RDD). We fail to find any statistically significant effect on research productivity and quality, which suggests that receiving an ERC grant does not make a difference in terms of scientific impact for researchers with a ranking position close enough to the threshold. Since RDDs help identify a local effect, we also conduct a difference-in-differences (DID) analysis using the time series of bibliometric indicators available, which allows us to estimate the effect on a wider population of winning and non-winning applicants. Differently from the RDD results, DID estimates show that obtaining an ERC grant leads to positive long-term effects on scientific productivity, impact and the capacity to attract other EU funds in the fields of Chemistry, Universe and Earth Sciences, Institutions and Behaviours, Human Mind Studies and Medicine. Further analysis of heterogeneous effects leads us conclude that the positive results obtained with DID seem to be driven by the top-ranked applicants in these fields.
Keywords: I23; D04; O3; 330; research grants; ERC; regression discontinuity design; difference in differences; EU funds; policy evaluation